Incongruence between gene trees and species trees and phylogenetic signal variation in plastid genes - Gonçalves, Deise J.P.; Simpson, Beryl B.; Ortiz, Edgardo M.; Shimizu, Gustavo H.; Jansen, Robert K. (Molecular phylogenetics and evolution, 2019)
[Display omitted] •Current classification of flowering plants is mostly based on plastid phylogenies.•Plastid phylogenies are inferred with full/partial genome and maximum likelihood.•Gene trees are often incongruent with the species tree inferred with plastid data.•Phylogenetic signal varies across plastid genes.•Data exploration helps to understand conflicting signal of plastid. The current classification of angiosperms is based primarily on concatenated plastid markers and maximum likelihood (ML) inference. This approach has been justified by the assumption that plastid DNA (ptDNA) is inherited as a single locus and that its individual genes produce congruent trees. However, structural and functional characteristics of ptDNA suggest that plastid genes may not evolve as a single locus and are experiencing different evolutionary forces. To examine this idea, we produced new complete plastid genome (plastome) sequences of 27 species and combined these data with publicly available sequences to produce a final dataset that includes 78 plastid genes for 89 species of rosids and five outgroups. We used four data matrices (i.e., gene, exon, codon-aligned, and amino acid) to infer species and gene trees using ML and multispecies coalescent (MSC) methods. Rosids include about one third of all angiosperms and their two major clades, fabids and malvids, were recovered in almost all analyses. However, we detected incongruence between species trees inferred with different matrices and methods and previously published plastid and nuclear phylogenies. We visualized and tested the significance of incongruence between gene trees and species trees. We then measured the distribution of phylogenetic signal across sites and genes supporting alternative placements of five controversial nodes at different taxonomic levels. Gene trees inferred with plastid data often disagree with species trees inferred using both ML (with unpartitioned or partitioned data) and MSC. Species trees inferred with both methods produced alternative topologies for a few taxa. Our results show that, in a phylogenetic context, plastid protein-coding genes may not be fully linked and behaving as a single locus. Furthermore, concatenated matrices may produce highly supported phylogenies that are discordant with individual gene trees. We also show that phylogenies inferred with MSC are accurate. We therefore emphasize the importance of considering variation in phylogenetic signal across plastid genes and the exploration of plastome data to increase accuracy of estimating relationships. We also support the use of MSC with plastome matrices in future phylogenomic investigations.